Exploitation of Hybrid Vigour in Indian Mustard in Absence of a Restorer Line - MANKAR KISHOR; N. C. SINGHAL; S. PRAKASH; ASHOK GAUR (Seed Research, 2026)
Heterosis was exploited in Indian mustard [(Brassica juncea L.) Czern & Coss] using hybrid and line composite (HLC) method by growing blended population of sterile F, (Pusa Barani oxy CMS x PSR 7) and male fertile line (PSR 7). Seven populations of blended seed in the ratios of 100:00, 90:10, 80:20, 70:30, 60:40, 50:50, 00:100 and two cultivars Pusa Barani and Pusa Bold were included in the experiment. The seed yield was found superior in 80:20 blending ratio in comparison of Pusa Barani (background of sterile F₁) and other blending ratios. In general, seed yield increased with increase in the proportion of heterotic (F,) plants in blended populations. Highest yield obtained in 100:00 (only sterile F,) blending ratio is only possible if pollen is available adequately in or around the field for pollination. HLC method can be used with any good pollinator which synchronises well during flowering. In comparison to three-line hybrid, it gives 5-6% lower yield. In absence of a restorer system a scheme for exploitation of hybrid vigour in Indian mustard is suggested.